Transforming Food, Embracing Inclusivity: Nepal’s Journey towards Sustainable Food Systems - Paudel, Rajesh; Nepali, P. B.; Panta, H. K.; Acharya, G. D. (Orchid Academia Siraha, 2023)
This study explored Nepal's dynamic food practices, examining the interplay between traditional rural and evolving urban contexts. The country's food system harmoniously integrates age-old agricultural wisdom with the changing demands of urbanization. In rural landscapes, communities craft a resilient tapestry using diverse crops, agroecological practices, and a profound respect for nature, ensuring steadfast food security even in challenging environments. Conversely, urbanization introduces convenience through supermarkets and processed foods, albeit with associated costs such as escalating health issues, food waste, and social inequalities. To bridge these disparities, a focus on inclusivity and resilience is imperative. Strategies include empowering rural women, investing in infrastructure, and safeguarding traditional knowledge for sustainable food security. Urban food policies should emphasize local markets, encourage healthy choices, and minimize waste. In essence, navigating Nepal's food system transformation necessitates a delicate balance between tradition and adaptation, aspiring towards a future where comprehensive food security and well-being flourish for all.